IMPROVING EMPLOYEE PERFORMANCE THROUGH JPB SATISFACTION: THE EFFECT OF TRAINING AND WORK ENVIRON: IMPROVING EMPLOYEE PERFORMANCE THROUGH JPB SATISFACTION: THE EFFECT OF TRAINING AND WORK ENVIRON - Rahmawan, Huda Setia; Husainah, Nazifah (PENANOMICS: International Journal of Economics, 2024)
The research aims to determine the effect of training and work environment on employee performance through job satisfaction as an intervening variable at PT. Sayusan Maritime Sailing. This research uses quantitative methods. The data used in this research is secondary data. The population in this research is the Company's employees, namely the ship's crew, totaling 133 people. The samples were selected from classifications based on age, length of work and educational status. The sample was selected using the Non Probability sampling method. Partial research results found that training has an effect on job satisfaction, training has no effect on employee performance, job satisfaction has no effect on performance, the work environment has a positive effect on job satisfaction, the work environment has no effect on performance, training and the work environment have no effect on performance through satisfaction work as an intervening variable.